Investment in Rural Broadband Technologies - Peter Stenberg (European Regional Science Association (ERSA), 2011)
Internet use has grown rapidly over the last two decades and so has the digital economy's integration into the rural economy. Connecting to the Internet via high-speed technology such as DSL lines, cable, satellite, and wireless networks increases bandwidth and makes the Internet much more useful to businesses, households, and governments. Rural communities have not been left out of the ever changing Information economy, though there has been an issue of equal access across the rural-urban milieu, but what is driving the investment of broadband Internet technologies in rural areas. We use recently collected data on broadband availability and historical economic and demographic data in our exploration of causal relationships. We use logistic regressions and the geographic levels of measurement are county and sub-county areas. Our analysis, consistent with profit-maximizing firm behavior, clearly shows the effect of population density and per capita income levels have on industry investment and indicate the challenges rural communities have in obtaining and maintaining modern Internet access.
Keywords: 330